The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/nu13082857
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinants of Sex-Specific Dietary Supplement Use in a Greek Cohort

Abstract: We describe the profile of dietary supplement use and its correlates in the Epirus Health Study cohort, which consists of 1237 adults (60.5% women) residing in urban north-west Greece. The association between dietary supplement use and demographic characteristics, lifestyle behaviors, personal medical history and clinical measurements was assessed using logistic regression models, separately for women and men. The overall prevalence of dietary supplement use was 31.4%, and it was higher in women (37.3%) compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 54 publications
6
24
1
Order By: Relevance
“…Our study showed that women used NSs, such as calcium and multivitamins, more often than men. This result is consistent with previous studies that have shown a higher interest in NS use among female consumers ( 25 27 ). Some researchers attribute this to women being more concerned than men about their health, as they feel more responsible for the wellbeing of other family members ( 2 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study showed that women used NSs, such as calcium and multivitamins, more often than men. This result is consistent with previous studies that have shown a higher interest in NS use among female consumers ( 25 27 ). Some researchers attribute this to women being more concerned than men about their health, as they feel more responsible for the wellbeing of other family members ( 2 ).…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have shown that NS users tend to maintain a healthy lifestyle, such as a balanced diet and regular exercise ( 32 , 34 , 36 ). We found that former smokers were more likely to use NSs, including protein and calcium, and that former smokers increased supplement use, possibly to minimize the adverse effects of their previous habits on their health ( 27 , 37 ). Past alcohol consumption was associated with the use of iron and zinc, and we suggest that this may be because most older people could not clearly distinguish between the effects of iron (a possible prooxidant) and zinc (a possible antioxidant) on cardiovascular disease and choose to avoid taking these supplements during periods of alcohol consumption ( 38 ).…”
Section: Discussionmentioning
confidence: 76%
“…CAM often was chosen by consumers instead of or in addition to antihypertensive medications [ 55 ]. Data of Epirus Health cohort study showed that women with chronic diseases are more likely to receive supplements, and also in this data DS use showed an inverse association with diastolic blood pressure in women [ 56 ].…”
Section: Discussionmentioning
confidence: 89%
“…It was administered from October 2020 to April 2021 through different online platforms, mainstream social media, and local press. In addition, participants of a population-based cohort study in northwestern Greece, the Epirus Health Study (EHS) [ 17 , 18 , 19 ], were also invited to complete the online survey. To guarantee anonymity, questions about personal data were avoided.…”
Section: Methodsmentioning
confidence: 99%